Perceived Stress and Burnout: The Mediating Role of Psychological, Professional Self-Care and Job Satisfaction as Preventive Factorsin Helping Professions - Hricova, Monika; Nezkusilova, Jana; Raczova, Beata (European Journal of Mental Health, 2020)
Background: Stress and burnout are among the common causes of absenteeism and fluctu - ation of staff in European workplaces. Therefore, the demand for understanding the predictors of burnout in high risk professions has been growing. The aim of this study is to explore the link between perceived stress and the three dimensions of burnout (emotional exhaustion, depersonalization, and personal accomplishment) while considering the potential mediating role of self-care and job satisfaction that may prevent the transformation of stress into burnout.Methods: A randomly selected group of Slovak social service professionals (N = 689; 618 women) from institutions in 8 districts in Slovakia described their levels of perceived stress, burnout, performed self-care and job satisfaction in self-reported questionnaires.Results: The relationship between stress and emotional exhaustion is solely mediated by certain aspects of job satisfaction: salary, nature of work, and operating procedures. The relationship between stress and depersonalization is mediated by the nature of work, psychological self-care, and professional self-care. However, professional self-care does not prevent but rather facilitates the development of depersonalization in times of high perceived stress. The relationship between stress and personal accomplishment is mediated by psychological and professional self-care as well as by three factors of job satisfaction: co-workers, nature of work and job benefits. When stress increases, satisfaction with co-workers and nature of work prevent the decrease of personal accomplishment. However, job benefits, with increasing stress, may be related to a decrease in personal accomplishment at work.Conclusion: Satisfaction with salary, nature of work, operating procedures and co-workers as well as psychological self-care may prevent the further development of burnout in times of high stress. Yet, professional self-care and job benefits may, in times of increased stress, potentially lead towards specific aspects of burnout (depersonalization and reduction of personal accomplishment).